Reforming Sufism in Malaya: The teachings of Tuan Tabal and his followers - Mohd Amin, Wan Mohd Azam (IIUM Press, 2013)
This paper examines the efforts made by ‘Abd al-Ṣamad ibn Ṣāliḥ (1840-1891) and his descendants, who were the members of the Aḥmadiyyah Idrīsī order (ṭarīqah), to reform Malay Sufism during the Nineteenth and Twentieth Century. Under the leadership of ‘Abd al-Ṣamad, the order attracted thousands of followers and its central issue was reforming the doctrine of “the unity of existence” by reconciling it with the “unity of consciousness” (waḥdat al-shuhūd), the teachings of Shaykh Ahmad Sirhindī (d.1624). The reform efforts continued by Wan Musa (1874-1939), Nik Abdullah (1900-1935) and Nik Muhammad Salleh (1920-1972). They, however, adapted the framework of Shāh Walī Allāh al-Dihlawī (1703-1762) ) in their undertakings.